Traditional Healing Expectations in Light of Placebo and Performance Studies - Kohonen, Siria (Folklore: Electronic Journal of Folklore, 2024)
This article examines what expectations lay people (those not considered folk healers themselves) had for pre-industrial Finnish-Karelian healing traditions, how these expectations were represented in archived folklore materials, and how they, in turn, affected the healing traditions. The study represents a cross-disciplinary analysis of the subject, with theoretical perspectives drawn from performance studies, cognitive science memory studies, and placebo studies. Via a two-step analysis, this article examines the different meanings given to traditional healing methods and suggests that these methods increased the placebo effect in several ways, most importantly by fulfilling the general expectations for healing performances. The article also proposes that the placebo effect affected the way that lay people considered efficacious healing performances. This article examines what expectations lay people (those not considered folk healers themselves) had for pre-industrial Finnish-Karelian healing traditions, how these expectations were represented in archived folklore materials, and how they, in turn, affected the healing traditions. The study represents a cross-disciplinary analysis of the subject, with theoretical perspectives drawn from performance studies, cognitive science memory studies, and placebo studies. Via a two-step analysis, this article examines the different meanings given to traditional healing methods and suggests that these methods increased the placebo effect in several ways, most importantly by fulfilling the general expectations for healing performances. The article also proposes that the placebo effect affected the way that lay people considered efficacious healing performances. Peer reviewed